Universal Urine Drug Screening with Rapid Confirmation upon Admission to Labor and Delivery - Haizler-Cohen, Lylach; Collins, Ana; Kaplan, Dana M.; Giri, Priyadarshani; Davidov, Adi; Blau, Jonathan; Fruhman, Gary (American Journal of Perinatology, 2023)
Objective This study aimed to describe our experience with universal urine drug screening (UDS) with rapid confirmation (RC) via liquid chromatography mass spectrometry (LC-MS) before infant's discharge, in efforts to increase detection of neonates at risk of neonatal opioid withdrawal syndrome (NOWS) while reducing patient burden related to false positive results.Study Design Two-phase retrospective study of all pregnant women admitted to our labor and delivery (L&D) unit before (phase 1, April 2018–March 2019) and after (phase 2, October 2019–September 2020) RC of UDS was initiated. Urine samples were obtained on admission and screened for drugs using an enzyme immunoassay with positive results reflexed to confirmation via LC-MS. The turnaround time for LC-MS was 1 week in phase 1 and 24 hours in phase 2. For mothers with positive LC-MS confirmation, the infant's meconium was sent for drug screening. Positive results were determined to be true or false positive based on urinary LC-MS results. The primary outcome was the rate of opioid-positive mothers who were unanticipated. The secondary outcome was the difference in rate of neonates who were observed for NOWS, before and after implementation of RC with LC-MS.Results In phase 2, a total of 2,395 deliveries occurred of which 2,122 (88.6%) had available UDS results. Fifty-two (2.5%) women had a positive UDS for at least one drug with LC-MS confirmation. Of those, 25 were true positive and 27 were false positive. Twenty-one (84%) true positive mothers were taking opioids and 8 (37%) of them were unanticipated positives. Among mothers with positive UDS for opioids, the neonatal observation rate for development of NOWS was 100% (22/22) and 48% (21/44) before and after implementation of LC-MS RC, respectively.Conclusion Universal UDS and LC-MS RC in L&D may improve detection of unanticipated positive mothers whose infants are at risk of NOWS. RC of positive results allows intervention only for confirmed cases.Key Points
Keywords: universal; urine; drug; screening; pregnancy; opioid